The synthesis of furofuranoid lignans - Stevens, David R. (1989)
An approach to the synthesis of 2,6-diaryl-8-oxo-3,7-dioxabicyclo [3,3,0] octane lignan lactones is presented and then used in the synthesis of the natural products aptosimon and styraxin. The structure of aptosimon has now been confirmed as having a 2,6-diaryl structure rather than the 2,4-diaryl structure which has been postulated in the literature. A germination inhibitor MEL, isolated from Aegilops ovata, has also been synthesised. A key ring closing reaction in this strategy was a Lewis acid catalysed directed aldol reaction between a silyl enol ether and an acetal. A review of similar ring closures in the literature is presented. The use of alpha-arylidene lactones as intermediates in lignin synthesis has also been investigated. The stereochemistry of products from reactions used in this strategy was determined and as a result it was possible to successfully design a stereochemically controlled synthesis of dihydrosesamin.